2002
DOI: 10.1038/ni830
|View full text |Cite
|
Sign up to set email alerts
|

CARMA1 is a critical lipid raft–associated regulator of TCR-induced NF-κB activation

Abstract: CARMA1 is a lymphocyte-specific member of the membrane-associated guanylate kinase (MAGUK) family of scaffolding proteins, which coordinate signaling pathways emanating from the plasma membrane. CARMA1 interacts with Bcl10 via its caspase-recruitment domain (CARD). Here we investigated the role of CARMA1 in T cell activation and found that T cell receptor (TCR) stimulation induced a physical association of CARMA1 with the TCR and Bcl10. We found that CARMA1 was constitutively associated with lipid rafts, where… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

18
281
1
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 319 publications
(301 citation statements)
references
References 49 publications
18
281
1
1
Order By: Relevance
“…CARMA1 has been recently identified as an essential component for the activation of transcription factor NF-jB upon antigen receptor activation in T and B cells [20][21][22]24]. In B cells, CARMA1 deficiency results in defective proliferation upon BCR stimulation and CARMA1 KO mice are defective in mounting humoral immune responses [20,23,24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CARMA1 has been recently identified as an essential component for the activation of transcription factor NF-jB upon antigen receptor activation in T and B cells [20][21][22]24]. In B cells, CARMA1 deficiency results in defective proliferation upon BCR stimulation and CARMA1 KO mice are defective in mounting humoral immune responses [20,23,24].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have identified a novel scaffold protein CARMA1 (CARD domain and membrane associated-guanylate kinase domain-containing protein-1) as an essential component involved in NF-jB activation upon antigenic stimulation in both T and B lymphocytes [19][20][21][22]. CARMA1-deficient B cells are defective in activation and proliferation upon BCR stimulation and in humoral immune responses [23,24].…”
mentioning
confidence: 99%
“…What is surprising however, as mentioned above, is the lack of a role for this complex in developing lymphocytes, and by extrapolation signaling through the pre-AgRs. The MAGUK family protein CARMA1 is required for activation of NF-kB in T cells following TCR ligation, but its loss has no effect on the development of thymocyte (Gaide et al, 2002;Egawa et al, 2003;Hara et al, 2003). Similarly, BCL10 is critical for NF-kB activation via the BCR and TCR, yet normal numbers of peripheral T cells are seen in BCL10 knockouts, and no clear defects in B-cell development is observed (Ruland et al, 2001).…”
Section: Role Of Nf-jb In the Adaptive Responsementioning
confidence: 99%
“…It is important to note that CARD scaffold proteins can signal through pathways other than NF-kB, such as Jun N-terminal kinase. 42,43 The identification of cSCC mutations in the CARD and GUK domains that abolish CARD11-mediated NF-kB activation yet maintain signalosome formation may be indicative of differential signaling. Similar variants in CARD14, which reduced NF-kB activation in 293 cells in vitro, also were identified in psoriasis patients, 24 therefore further work will be needed to determine whether CARD11 and CARD14 do indeed mediate differential signaling in keratinocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Another possibility is that cSCC variants that abolish NF-kB activation reflect the published contextdependent role of NF-kB signaling in keratinocytes 10,11,44 and, given the correct context, reduction of NF-kB signaling through CARD11 mutation may be tumor promoting. Those CARD11 variants that abolish NF-kB activation may result from disruption of essential proteineprotein interactions such as association with BCL10 40,43 and PDK1, 39 both of which are crucial for pathway activation.…”
Section: Discussionmentioning
confidence: 99%